ANALYSIS OF THE FEEDING OF FISH AND FISH SKIN WASTE TO THE GROWTH AND RETENTION OF PROTEIN IN DUMBO CATFISH (Clarias gariepinus) - Mubarok, Muh. Tsabit; Jumadi, Rahmad; Rahim, Andi Rahmad (Jurnal Perikanan Pantura (JPP), 2020)
African catfish is the leading commodity in Indonesia, which has a speed of growth and is resistant to adverse environmental conditions. Trash fish is a small-sized fish such as fish, stingrays, rebon, turmeric fish and the like, Trash fish is also a fish that has a very low economic value. Trash fish has a protein content of 28.28%. Fish skin is the result of sampling from slaughtering animals in the form of body organs during the process of difficulty. Waste of fish skins in the place of fish milling usually consists of several types of fish including grouper, payus, cob, catfish, catfish, white fish and brass fish. Fish skin waste has 26.9% protein. The purpose of this study was to determine the effect of trash fish feeding and fish skin waste feeding on the growth and protein retention of African catfish (Clarias gariepinus). Knowing the effect of feeding combined trash fish and fish skin waste on FCR of African catfish (Clarias gariepinus). This study used a completely randomized design (CRD) consisting of 4 treatments and 3 replications with the following measurements: (A - trash fish feed 5.3%), (B - fish skin waste 5.77%), (C - (fish trash (50%) + fish skin waste (50%) with 5.55% administration, (K - Pellet 100% Control 5%). Main parameters include Absolute weight growth (grams), Specific growth rate (%), Length Absolute (cm), protein retention, survival and feed conversion ratio (FCR), while supporting parameters include temperature, pH, DO, ammonia, salinity.Research results were analyzed using SPSS version 17. Each data in the form of growth, survival and feed conversion ratio (FCR) was analyzed using ANOVA (Analysis of Variance) with a confidence level of 95%, if significance (P <0.05) continued with the Tukey test (HSD) to see differences between treatments Water quality data and protein retention (% ) analyzed descriptively based on literature The results of research with pe feed of trash fish and fish skin as well as combination of trash fish (50%) + fish skin waste (50%), for the best absolute weight is the treatment K (Control) with a value of 21.03 g. The best daily growth rate is in the treatment K (Control) with a value of 1.96% / day. The absolute length rate is in the K (Control) treatment with a value of 3.20cm. The best retention value is the treatment K (Control) with a value of 36.32%. The lowest feed conversion ratio / FCR is control K at 1.78 g, while for the best survival (%) is treatment B (fish skin waste) with 90% survival.